Understanding consumers to inform market interventions for Singapore's shark fin trade - Choy, C; Booth, H; Veríssimo, D (Wiley, 2024)
1. Sharks, rays and their cartilaginous relatives (Class Chondrichthyes, herein ‘sharks’) are among the world's most threatened species groups, primarily due to overfishing, which in turn is driven by complex market forces including demand for fins. Understanding the high-value shark fin market is a global priority for conserving shark and rays, yet the preferences of shark fin consumers are not well understood. This gap hinders the design of evidence-based consumer-focused conservation interventions.